Penerapan Pembelajaran Aktif melalui Permainan Tradisional Gobak Sodor di SMA Negeri 3 Sumenep - Sri Rahayu Wulandari; Winda Nurasiyah; Dian Helaprahara (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the significance of the traditional game of Gobak Sodor in the educational context of a high school (SMA Negeri 3 Sumenep), particularly regarding the development of students’ fundamental motor skills and the role of teachers in its preservation. Gobak Sodor, as a cultural heritage, is valued not only as a recreational activity but also as an educational medium rich in local, social, and physical values. The research methods employed involved data collection through observation, interviews, and a review of empirical literature (2020–2024). The results and discussion are divided into three main focuses. First, the significance of Gobak Sodor has been proven effective in improving agility and gross motor skills, as well as fostering social character values such as mutual assistance, teamwork, and solidarity. Second, the Impact of Gobak Sodor on Fundamental Movements indicates that this game significantly contributes to improving the locomotor, non-locomotor, and manipulative skills of students at State High School 3 Sumenep, while also enhancing physical fitness and problem-solving abilities. Third, the role of teachers is emphasized as a crucial factor in integrating and promoting Gobak Sodor into the Physical Education (PJOK) curriculum through innovative strategies, collaboration with parents, and the use of technology, to ensure the sustainability of cultural preservation amidst the challenges of the digital age. Overall, this study confirms that Gobak Sodor is a holistic and essential learning medium in supporting students’ physical and social development as well as character building.